Combinatorial Algorithms 21st International Workshop, IWOCA 2010, London, UK, July 26-28, 2010, Revised Selected Papers - Iliopoulos, Costas S.; Smyth, William F. (Springer eBooks., 2011)
This book constitutes the thoroughly referred post-proceedings of the 21st International Workshop on Combinatorial Algorithms, IWOCA 2010, held in London, UK, in July 2010. The 31 revised full papers presented together with extended abstracts of 8 poster presentations were carefully reviewed and selected from a total of 85 submissions. A broad variety of combinatorial graph algorithms for the computations of various graph features are presented; also algorithms for network compuation, approximation, computational geometry, games, and search are presented and complexity aspects of such algorithms are discussed.